Between Rationality and Uncertainty: Exploring the Finest Strategy to Manage Disaster Governance and Budgetary Perspective - Bambang Supriyono; Oscar Radyan Danar (Journal of Governance and Public Policy, 2022)
Massive damage and loss of natural hazards occurred in Indonesia, raising numerous questions about the government's capacity to minimize disaster risk through appropriate disaster governance strategy. This article explores the strategy to manage the disaster and budgetary mechanism currently underpinned by the rationalist principle. However, during the dynamic situation and high degree of uncertainty, the effectiveness and efficiency of the rationalist principle remain questionable. It has been supported by a set of notorious consequences of the disaster that the government has undertaken in recent years. Therefore, by using a qualitative approach, this article aims to seek the performance's description and shortcomings of current strategy based on theoretical analysis and literature study. The findings illustrate the vague mechanism, particularly local disaster strategy, political decision-making, and flexibility of reimbursement mechanisms. Finally, this article also gives a specific recommendation for policymakers to give plenty of space for a current strategy to be more adaptive toward any turbulences in the future.